CHARACTERIZATION OF TRANSVERSE CYLINDRICAL CAVITIES IN WOODEN BLOCKS OF THE SPECIES Cedrela odorata USING NON-DESTRUCTIVE ULTRASOUND TESTS - Yoza Yoza, Luis Shuseki; Allende, Erik Baradit; Cruz, Oscar Enrique Tang; Matos, Jorge Luis Monteiro de; Rocha, Márcio Pereira da; VENSON, IVAN (Floresta, 2021)
The main objective of the present work was to characterize the transverse cylindrical cavities of Cedrela odorata wood blocks using the non-destructive ultrasound techniques (NDT). The dispersions of acoustic wave propagation velocity (AWV) were measured and, considering the anisotropic structure of the wood, the Hankinson model was used for modeling with 2D graphics. The results showed strong dispersion in the frontal direction depending on the diameter of the cavities, in addition to good linear relationships between them for the cavity axis. Therefore, the results support the use of NDT ultrasound techniques to assess deteriorated structural elements such as historical monuments.